APLIKASI DATA BUOY DAN DATA PASANG SURUT UNTUK PENENTUAN SUMBER GEMPA,WAKTU TIBA, DAN TINGGI GELOMBANG TSUNAMI BENGKULU 2007 - ILLIEN P. , DIAN
Bengkulu Tsunami,which was generated by earthquake with 8,5 Richter magnitude on September 12th,2007 at 18:10:26 (local time) in location Latitude 4.520 derajat S and Longitude 101.374 derajat E. This final report simulates the generation model and the propagation tsunami waveforms with two models that is single fault model and distribution heterogenous slip model result by inversion. The data used is bathymetri data, earthquake data source and wave elevation data source from buoy stations and tide gauge in Sumatera. From those data, it can be determined by the value of the earthquake homogenous slip and then performed the propagation of tsunami. The single fault is divided into small areas.With the inversion method can be obtained a new value heterogenous slip. Results obtained from these two models, single fault model and distribution heterogenous slip model result by inversion then compared with observed data from buoy stations and tide gauge. Results obtained from the calculation of the simulation model using the value of a heterogenous slip has gave a good output. In the heterogen distribution slip heterogen model the result close to observation data due to subfault which smaller that make higher resolution,but this method also has lach which is high resolution that make slip stability distribution less.